Experiencing the middle : an investigation into the experiential qualities of site, space and materials - Van den Berg, Anton (School of Architecture, Planning and Geomatics, 2016)
My architectural thesis investigation stems from an interest in the materiality of architecture and the "life-giving" characteristics that materials can have in capturing the character or essence of a place. As this interest has developed, I have simultaneously developed an appreciation for the phenomenological and sensorial opportunities and possibilities that lie within the nature of a site and how these opportunities can be utilized to enhance the experience of the site through architecture. Each site contains quantitative phenomena, but also contains more ethereal phenomena such as 'feelings' and emotions, which often leave a longer-lasting impression and spiritual connection to a place, rather than a mere formal recognition. For example, being within a cool, dense and dark forest; with tall and towering trees above; with old, crunching leaves below or out in the soft open field, with the warm sun beaming down and one or two clouds slowly drifting overhead, on the same piece of mountain side, will have vastly different sensorial characteristics and moments, whilst still being connected to a greater site, which carries its own qualitative elements. These feelings and emotional connections to the site are dynamic and temporal, as they will also fluctuate according to day/ night or weather/ season. I find the process of approaching design through this conceptual filter extremely exciting, as one is constantly thinking about and engaging with the body of the user. It is important to find, through processes of 'experiential mapping', specific characteristics and moments, which inform the programming of a site. Questions are constantly asked as to what the body will See; Smell; Hear; Taste; Touch or Feel and Think; as the user moves through the site and space. Architecture is therefore given back to the body, contrasting the formal fascination and abstraction which occurred during the Modernist movement. How does one then capture these less tangible phenomena architecturally and engage the senses of the user? Spatially these opportunities can be materialized through the amalgamation of, and complementing and contrasting expressions of site specific phenomena such as: - textures; - light / shadows; - cool/ warmth; - sound'; - materials; - enclosures / voids-static / dynamic ; - flow of contours;